2002
DOI: 10.1149/1.1447946
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Si(111)-SiO[sub 2], Si(110)-SiO[sub 2], and Si(100)-SiO[sub 2] Interfacial Properties Following Rapid Thermal Annealing

Abstract: The purpose of this article is to report the results of an experiment designed to investigate the density of interface states (DOS) measured at the normalSi­SiO2 interface immediately following rapid thermal annealing (RTA) (1040°C) in a nitrogen false(N2false) ambient. This work extends previous publications on Si(100) by examining (111), (110), and (100) silicon orientations. The DOS profiles were examined using a mercury probe capacitance-voltage technique, and characteristic peaks in the DOS across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…This could explain why the distribution of the interface density of state across the energy gap for the ͑100͒Si/ SiO 2 system is asymmetric in the lower half of the band gap while it is symmetric in the upper half. 13,19 It could also explain why for the ͑111͒ and ͑110͒ silicon, the density of states peaks in the lower and upper gaps have almost the same magnitudes while for ͑100͒, they do not. 13 On the other hand, it is known that under nonequilibrium conditions, some occupancies of the single-electron state of the negative-U defect can be observed.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain why the distribution of the interface density of state across the energy gap for the ͑100͒Si/ SiO 2 system is asymmetric in the lower half of the band gap while it is symmetric in the upper half. 13,19 It could also explain why for the ͑111͒ and ͑110͒ silicon, the density of states peaks in the lower and upper gaps have almost the same magnitudes while for ͑100͒, they do not. 13 On the other hand, it is known that under nonequilibrium conditions, some occupancies of the single-electron state of the negative-U defect can be observed.…”
Section: -mentioning
confidence: 99%
“…13,19 It could also explain why for the ͑111͒ and ͑110͒ silicon, the density of states peaks in the lower and upper gaps have almost the same magnitudes while for ͑100͒, they do not. 13 On the other hand, it is known that under nonequilibrium conditions, some occupancies of the single-electron state of the negative-U defect can be observed. 20 As a result, depending on the experimental conditions, some disturbances of equilibrium could explain the controversy as to whether the P b1 center has an energy level in the Si band gap.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively lower surface state density at the C 10 H 21 ÀSi interface indicates that the organic modification of atomically flat hydrogen-terminated silicon does not generate a substantial number of electronic states at the alkyl monolayer j silicon interfaces, which is consistent with previous studies of C 18 H 37 ÀSi and Si(111)ÀSiO 2 interfaces. [17,37] The comparison between the densities of the surface states in these two types of mercury ± silicon junctions also helps us to understand further the difference in the determined effective barrier heights. Although the two junctions were fabricated from the same metal and semiconductor, but in a real diode, the barrier height f b was also greatly affected by the density of the surface states and the interfacial insulating layer (beyond its contribution as an electron tunneling barrier, as discussed previously).…”
Section: à2mentioning
confidence: 99%
“…It is noted that this D it − E g calculation is derived from HFCV data, measured at 1 kHz and not from a QSCV. However, it has been shown that the density of states profile as evaluated from HFCV follows the QSCV signal for samples with such anomalous peak features [17]. The integrated density (in the energy range 0.6 eV < E < 1.0 eV) corresponding to this interface defect in the e-beam evaporated sample is 9 × 10 11 cm −2 .…”
Section: Results and Discussion-impact Of Metal On The Underlyinmentioning
confidence: 92%